1998
DOI: 10.2307/2491478
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Taxes on the Structure of Corporate Acquisitions

Abstract: INFORMATION TO USERSThis manuscript has been reproduced from the microfihn master. UMI films the text directly from the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer.The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 22 publications
5
78
0
5
Order By: Relevance
“…In more detail, our results indicate (variables ΔTASS, ΔOPINC, ΔPLBT and ΔNETIN) that the new GITC provides further opportunities for capital gains, which are not subject to tax from mergers. Similar results that merger transactions may be affected by the Income Tax Code or capital gains tax policy was found in the study of Erickson (1998), Ayers et al (2007), Belz et al (2013) and Edwards et al (2016), while other studies do not claim that there is an important alignment of the merger decision and the taxation issues in the business arena (Auerbach and Reishus, 1987a;Breen, 1987;Devos et al, 2008) (Table 5). Scholes and Wolfson (1990) support that the changes of taxation are partially connected to the effects of a merger decision and tax issues.…”
Section: Mergers and Impact Of The New Greek Income Tax Codesupporting
confidence: 65%
See 1 more Smart Citation
“…In more detail, our results indicate (variables ΔTASS, ΔOPINC, ΔPLBT and ΔNETIN) that the new GITC provides further opportunities for capital gains, which are not subject to tax from mergers. Similar results that merger transactions may be affected by the Income Tax Code or capital gains tax policy was found in the study of Erickson (1998), Ayers et al (2007), Belz et al (2013) and Edwards et al (2016), while other studies do not claim that there is an important alignment of the merger decision and the taxation issues in the business arena (Auerbach and Reishus, 1987a;Breen, 1987;Devos et al, 2008) (Table 5). Scholes and Wolfson (1990) support that the changes of taxation are partially connected to the effects of a merger decision and tax issues.…”
Section: Mergers and Impact Of The New Greek Income Tax Codesupporting
confidence: 65%
“…Thus, their findings suggested that for every dollar taxed, shareholders were asking for 20 cents in the stock price for their capital gains. Erickson (1998) approaches the structure of corporate acquisitions from the perspective of investment finance, and provides evidence that the tax regime of M&As affects the way in which these transactions take place. A sample of 344 business acquisitions completed between 1985 and 1988 from a variety of sources was collected.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, Erickson (1998) finds little evidence of E&P elimination at acquisition among publicly-traded companies. Analyzing 340 acquisitions from 1985-1988 involving publicly traded acquirers and targets, Erickson (1998) reports only seven acquirers disclosed their intention to step-up the tax basis of the target's assets.…”
Section: Do Firms Eliminate Eandp and Avoid Dividend Taxation?mentioning
confidence: 96%
“…124 Huizinga and Voget (2009) The evidence on shareholder taxation and merger pricing is mixed. 125 Erickson (1998) finds no evidence that target shareholder tax liabilities affect acquisition price, which he attributes to 123 See Crowell Moring Financial Services Alert dated October 6, 2008 "Tax Notice Drives Wachovia Takeover Turmoil" about the IRS changing the loss limitation rules for banks and the immediate entrance of Wells Fargo as the acquirer of Wachovia at a much higher price than the agreed price for the same acquisition by Citigroup. 124 An important implication of this analysis is that the owners consider the method and timing of exiting the investment when choosing an organizational form.…”
mentioning
confidence: 99%